Circular RNA ITCH Is a Tumor Suppressor in Clear Cell Renal Cell Carcinoma Metastasis through miR-106b-5p/PDCD4 Axis - Ping Gao; Yong Huang; Yanmei Hou; Qian Li; Haimei Wang (Journal of Immunology Research)
High metastasis of clear cell renal cell carcinoma (ccRCC) significantly influenced survival rate of ccRCC patients. Here, we intended to investigate the impacts of circular RNA ITCH (circ-ITCH) on the metastasis of ccRCC. The expression of circ-ITCH in ccRCC tissues and cells was evaluated utilizing qRT-PCR. Transwell assay and wound healing were applied to investigate migration and invasion of ccRCC cells. Target gene prediction and screening and luciferase reporter gene assays were utilized to assess downstream target genes of circ-ITCH. Western blot was utilized to detect metastasis-related protein expression. A xenograft tumor model was established to evaluate the role of circ-ITCH in vivo. Results showed that circ-ITCH was low expressed in ccRCC tissues and cells. Downregulation circ-ITCH promoted cell migration, but overexpressing circ-ITCH inhibited cell migration and invasion in OSRC-2 and SW839 cells. Mechanism investigations claimed that circ-ITCH exerted its metastasis-inhibitory activity via sponging miR-106b-5p and regulating the expression of PDCD4. Conclusively, circ-ITCH suppresses ccRCC metastasis by enforcing PDCD4 expression through binding miR-106b-5p. circ-ITCH may function as a novel diagnostic target to suppress ccRCC metastasis.